2022
DOI: 10.1038/s42004-022-00784-3
|View full text |Cite
|
Sign up to set email alerts
|

Cr2+ solid solution in UO2 evidenced by advanced spectroscopy

Abstract: Advanced Cr-doped UO2 fuels are essential for driving safe and efficient generation of nuclear energy. Although widely deployed, little is known about their fundamental chemistry, which is a critical gap for development of new fuel materials and radioactive waste management strategies. Utilising an original approach, we directly evidence the chemistry of Cr(3+)2O3–doped U(4+)O2. Advanced high-flux, high-spectral purity X-ray absorption spectroscopy (XAS), corroborated by diffraction, Raman spectroscopy and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Complete digest of the pellets sintered at 1700 °C showed that the Cr content was below the expected, nominal, Cr concentration (Fig. 1b), which is attributed to volatilisation at the high sintering temperature 9,31,32 .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Complete digest of the pellets sintered at 1700 °C showed that the Cr content was below the expected, nominal, Cr concentration (Fig. 1b), which is attributed to volatilisation at the high sintering temperature 9,31,32 .…”
Section: Resultsmentioning
confidence: 92%
“…The microstructure and defect chemistry of the Cr-doped UO 2 materials utilised in the dissolution experiments was detailed fully by Smith et al 9 . Briefly, for all concentrations of Cr-doped UO 2, the sintered pellets presented a homogenous distribution of Cr 2+ within the UO 2 matrix, charge compensated by O v defects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been proposed the possibility of Cr +2 occurring within the UO 2 lattice matrix itself with some redox mechanisms between it and Cr +3 which should be observable at ambient conditions. 8 , 48 We note relevant studies to this argument have only investigated bulk material at ambient conditions which carries significant deconvolution in Cr measurement, as demonstrated by Fig. 2 b and c regarding the difference between bulk and lattice structure, respectively.…”
Section: Discussionmentioning
confidence: 99%